Maintaining (locus of) Control? Assessing the impact of locus of control on education decisions and wages - Rémi Piatek; Pia R. Pinger (Verein für Socialpolitik, 2010)
This paper establishes that individuals with an internal locus of control, i.e. who believe that reinforcement in life comes from their own actions instead of being determined by luck or destiny, earn higher wages. However, this positive effect only translates into labor income via the channel of education: once schooling is controlled for, the impact of locus of control on wages vanishes. Factor structure models are implemented on an augmented data set coming from two different samples. By so doing, we are able to tackle measurement error and endogeneity problems that plague many studies relying on usual least squares approaches.
Keywords: C31; J24; J31; 330; locus of control; wages; latent factor model; data set combination